Charting the Path Forward: Development, Goals and Initiatives of the 2019 Infectious Diseases of America Strategic Plan. (17th October 2019) - Sears, Cynthia L; File, Thomas M; Alexander, Barbara D; McQuillen, Daniel P; MacIntyre, Ann T; Allen, Upton D; Colasanti, Jonathan A; Siddiqui, Javeed; Reveles, Kelly R; Busky, Chris; ,
Abstract: In October 2018, the Infectious Diseases Society of America (IDSA) Board of Directors (BOD) decided to develop a 2019 IDSA Strategic Plan. The IDSA BOD has invested in strategic planning at regular intervals as part of an ongoing process to review and to renew the vision and direction of IDSA. Herein, the 2018–2019 strategic planning process and outcomes are described. The 2019 IDSA Strategic Plan presents 4 key initiatives: (1) optimize the development, dissemination, and adoption of timely and relevant ID guidance and guidelines that improve the outcomes of clinical care; (2) quantify, communicate, and advocate for the value of ID physicians to increase professional fulfillment and compensation; (3) facilitate the growth and development of the ID workforce to meet emerging scientific, clinical, and leadership needs; and (4) develop and position a new tool to serve as the leading US benchmark to measure and drive national progress on antimicrobial resistance. The BOD looks forward to developing, implementing, assessing, and advancing the 2019 IDSA Strategic Plan working with member volunteers, Society partners, and IDSA staff. Abstract : Through a deliberative process that involved substantive input from volunteer leaders and the IDSA membership, IDSA has created a new Strategic Plan to guide the Society over the next several years, presenting 4 initiatives using the "Run, Grow, Transform" strategic model.